Is there a “victim syndrome” among forced displaced persons in Ukraine? - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O.; Тімченко, Олександр Володимирович; Тімченко, О. В.; Тимченко, Александр Владимирович; Timchenko, Oleksandr V.; Христенко, Віталій Євгенович; Христенко, В. Є.; Христенко, Виталий Евгеньевич; Khrystenko, Vitalii Ye.; et al. (Hampstead Psychological Associates, 2020)
For the first time, a more specific definition is proposed for refugees who are forced to change their place of residence within their own country for reasons beyond their control, due to military conflict or other reasons, namely, “forced displaced persons”. The new definition more fully, correctly and adequately describes the life situation and position of this category of people. This study revealed the negative health effects of forced displaced persons who were resettled to the other region inside Ukraine due to a military conflict in the east of the country. To study both pre-migration traumatic influence and the negative consequences of relocation, three instruments were used: A. Bass and A. Darki technique for diagnosing indicators and forms of aggression, E. Wagner projective hand test and A. M. Etkind’s Relationship Color Test. The results of a sample of Ukrainian forced displaced persons (n=3500) indicate that they have fear, confusion, lack of feeling safety in the near future and dissatisfaction with one of the basic needs – security need. It was established that 7-8% of forced displaced persons have recorded “victim syndrome”, which develops in a situation when a person has lost hope of returning home in the near future and is in a state of constant heightened anxiety. It has been revealed that the “victim syndrome” among forced displaced persons is simultaneously characterized by increased aggressiveness towards others (primarily state structures), as well as the presence of «learned helplessness» and a general negative attitude towards everything that happens in the environment and in life of the refugee. The results of this study will permit to strengthen the potential of the social system in the host community and invest in the planning of health services and the social integration of displaced persons which were resettled not only within the territory of their native country, but also for those who migrated to other national societies.

Вперше пропонується більш конкретне визначення для біженців, які змушені змінити місце проживання в межах своєї країни з причин, що не залежать від них, внаслідок воєнного конфлікту чи інших причин, а саме „вимушених переселенців”. Нове визначення більш повно, правильно та адекватно описує життєву ситуацію та становище цієї категорії людей. Це дослідження виявило негативні наслідки для здоров'я вимушених переселенців, які були переселені в інший регіон всередині України через військовий конфлікт на сході країни. Для вивчення як міграційного травматичного впливу, так і негативних наслідків переселення використовувались три інструменти: методика А. Басса та А. Даркі для діагностики показників та форм агресії, проєктивна методика дослідження особистості Е. Вагнера та кольоровий невербальний тест відносин А. М. Еткінда. Результати вибірки українських вимушених переселенців (n = 3500) вказують на те, що вони мають страх, розгубленість, відсутність почуття безпеки найближчим часом та незадоволення однією з основних потреб - потребою в безпеці. Було встановлено, що у 7-8% вимушених переселенців зафіксували «синдром жертви», який розвивається в ситуації, коли людина втратила надію повернутися додому найближчим часом і перебуває у стані постійно підвищеної тривоги. Виявлено, що «синдром жертви» серед вимушених переселенців одночасно характеризується підвищеною агресивністю по відношенню до інших (насамперед державних структур), а також наявністю «придбаної безпорадності» та загальним негативним ставленням до всього, що відбувається в навколишньому середовищі та в житті біженця. Результати цього дослідження дозволять посилити потенціал соціальної системи в приймаючій громаді та інвестувати в планування медичних послуг та соціальну інтеграцію переміщених осіб, які були переселені не лише на територію рідної країни, а й для тих, хто мігрував до інших національних товариств.

Впервые предлагается более конкретное определение для беженцев, которые вынуждены изменить место проживания в своей стране по независящим от них причинам, из-за военного конфликта или по другим причинам, а именно «вынужденно перемещенных лиц». Новое определение более полно, правильно и адекватно описывает жизненную ситуацию и положение данной категории людей. Это исследование выявило негативные последствия для здоровья вынужденных переселенцев, которые были переселены в другой регион Украины из-за военного конфликта на востоке страны. Для изучения как травмирующего миграционного воздействия, так и негативных последствий переселения использовались три инструмента: методика А. Басса и А. Дарки для диагностики показателей и форм агрессии, проективная методика исследования личности Э. Вагнера и цветовой невербальный тест отношений А. М. Эткинда. Результаты выборки украинских вынужденных переселенцев (n = 3500) показывают, что у них есть страх, растерянность, отсутствие чувства безопасности в ближайшем будущем и неудовлетворенность одной из основных потребностей - потребностью в безопасности. Установлено, что у 7-8% вынужденных переселенцев зафиксирован «синдром жертвы», который развивается в ситуации, когда человек потерял надежду вернуться домой в ближайшее время и находится в состоянии постоянной повышенной тревоги. Выявлено, что «синдром жертвы» у вынужденных переселенцев одновременно характеризуется повышенной агрессивностью по отношению к другим (в первую очередь к государственным структурам), а также наличием «приобретенной беспомощности» и общим негативным отношением ко всему, что происходит в окружающем мире и в жизни беженца. Результаты этого исследования позволят усилить потенциал социальной системы в принимающем сообществе и инвестировать в планирование медицинских услуг и социальную интеграцию перемещенных лиц, которые были переселены не только на территорию своей родной страны, но и в другие страны.
Timchenko О. There a “victim syndrome” among forced displaced persons in Ukraine? / O. Timchenko, V. Khrystenko, V. Lefterov, et al. // International Journal of Psychosocial Rehabilitation. – V. 24 (6). - Hampstead Psychological Associates, 2020. – P. 13092-13110.
Keywords: forced displacement; Ukrainian internally displaced persons; victim syndrome; learned helplessness; anxiety; lack of safety; вимушене переселення; українські внутрішньо переміщені особи; синдром жертви; придбана безпорадність; тривога; незахищеність; принудительное перемещение; украинские внутренне перемещенные лица; синдром жертвы; приобретенная беспомощность; тревога; незащищенность; Research Subject Categories::LAW/JURISPRUDENCE